PEMANFAATAN KITOSAN DARI CANGKANG BEKICOT (Achatina fulica) SEBAGAI PENGAWET IKAN KEMBUNG (Rastrelliger sp) DAN IKAN LELE (Clarias batrachus) - Sari Wahyu Waryani; Rika Silvia; Farida Hanum (Talenta Publisher (Universitas Sumatera Utara), 2014)
The efforts that should be made to maintain the quality of fish is by using antimicrobial compounds, one of which is chitosan. In this research, characterization of chitosan from shell snail (Achatina fulica) has a water content of 5.07%, ash content of 1.8% and the degree of deacetylation (DD) 75.13%. The use of chitosan in this study was to determine the optimal conditions on chitosan concentration and storage time of mackerel (Rastrelliger sp) and catfish (Clarias batrachus) from the microbiological and organoleptic aspects. This research used a variation of the concentration of chitosan was 1%, 1.5%, 2% and 2.5% dissolved in 1% acetic acid. Observations were do with variation the storage time 10 hours, 15 hours, 20 hours and 25 hours and the provision of chitosan solution by soaking and spraying with the observation parameters Total Volatile Base (TVB), organoleptic and pH of fish. Based on the analysis, the results showed that the maximum concentration of chitosan on mackerel (Rastrelliger sp) and catfish (Clarias batrachus) is 1,5% and treatment by means of immersion is the best treatment. The use of chitosan solution on mackerel (Rastrelliger sp) survived 20 hours while catfish (Clarias batrachus) survived 15 hours.